Kualitas pelayanan terhadap kepuasan pasien rawat jalan menggunakan metode servqual di Puskesmas Tawangrejo - Intan Septyaningrum; Riska Ratnawati; Retno Widiarini (Poltekkes Kemenkes Aceh, 2024)
Background: Based on the minimum service standard that must be achieved, namely ≥ 90%, however the level of patient satisfaction has not yet reached the Minimum Service Standard (SPM) of 84,98 and there are several complaints from several patients regarding health services, there are still officers who are less friendly and polite to patients and lack of health center staff.Objective: The research aims to analyze the influence of service quality on outpatient satisfaction using the servqual method.Method: This research uses a cross sectional study design. The total sample was 96 respondents with a sampling technique using Proportional Random Sampling. The research location was carried out at the Tawangrejo Community Health Center in 2023. Data collection used a questionnaire and was based on patient visit data. Data processing uses editing, coding and data entry. Analysis used univariate and bivariate analysis with chi-square test using SPSS 16,0Results: The results of data processing using the Chi-Square test show that the p value is 0,040 < α = 0,005, showing a PR value of 2,759 and a value (95% CI = 1,134 – 6,711) which means there is a relationship between service quality and outpatient satisfaction. in the Tawangrejo Community Health Center Working Area.Conclusion: There is an influence between service quality on outpatient satisfaction in the Tawangrejo Community Health Center Working Area. It is hoped that the suggestions given by the Tawangrejo Community Health Center can further maintain and improve the quality of services that have been provided so far and immediately improve patient complaints.KeywordsService Quality, Patient Satisfaction, Outpatient Care